2013
DOI: 10.1016/j.ecoenv.2013.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risks of polycyclic musk in soils irrigated with reclaimed municipal wastewater

Abstract: a b s t r a c t HHCB (1,3,4,6,7,6,6,7, and 1,3,4,4,2,3, are found in reclaimed municipal wastewater. They may accumulate in soils receiving long-term application of reclaimed water thus adversely impact the soil biota. We evaluated the extent of their accumulation in receiving soils using HYDRUS-1D based on reclaimed municipal wastewater irrigation data at a public park in Beijing. The potential for ecological harms were assessed according to tested and reported outcomes of acute toxicity tests using wheat (Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Due to its relative high-level salts compared to tap water, reclaimed water irrigation has led to soil property deterioration and affected plant growth (de Miguel et al 2013;Pedrero et al 2014). Accumulations of toxic substances such heavy metals and musk in soils receiving reclaimed water sometimes are also noticed (Chen et al 2013a;Kang et al 2007;Wang et al 2013). The enhanced soil biological activities have been observed due to the extra nutrients from the reclaimed water, whereas the adverse effects on soil biological activities can also occur because of harmful trace substances in reclaimed water (Brzezinska et al 2001;Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relative high-level salts compared to tap water, reclaimed water irrigation has led to soil property deterioration and affected plant growth (de Miguel et al 2013;Pedrero et al 2014). Accumulations of toxic substances such heavy metals and musk in soils receiving reclaimed water sometimes are also noticed (Chen et al 2013a;Kang et al 2007;Wang et al 2013). The enhanced soil biological activities have been observed due to the extra nutrients from the reclaimed water, whereas the adverse effects on soil biological activities can also occur because of harmful trace substances in reclaimed water (Brzezinska et al 2001;Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Madrid City Council replaced the usual drinking water irrigation system by a reclaimed water one, in most of its green areas. Reclaimed water irrigation is also carried out by other large cities in the world, such as Beijing (China) (Yi et al, 2011;Wang et al, 2013), Denver and San Diego (USA) (Qian & Mecham, 2005;San Diego City Council, 2019), Adelaide (Australia) (Nouri et al, 2013) and Tokyo (Japan) (Furumai, 2008). Nowadays, in Madrid there are over 30 green areas irrigated with reclaimed water coming from its water reclamation plants.…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation with contaminated water [5,6] or fertilization with biosolids from wastewater treatment plants [7,8] may be possible origins of soil contamination. Nevertheless, literature has shown that over the past decades several organic contaminants like pharmaceutical and personal care products (PCPs) are present either in biosolids or in treated wastewater [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' best knowledge, the UVFs under scrutiny in this paper have been mostly studied in specific soils, like beach sand, and few studies are available regarding SMCs. Analyzing the available works, soil samples were generally extracted and cleaned up either by ultrasound (USE), vortex, on-column lixiviation [14], SPME [14][15][16], pressurized liquid extraction (PLE) [6,[17][18][19][20][21], stir-bar sorptive extraction (SBSE) [22], SPE [23], or using a solid-liquid extraction approach (SLE) [24,25]. Although PLE, SBSE, and SPME are methods with good performances, the equipment required is not always available in all laboratories.…”
Section: Introductionmentioning
confidence: 99%